AB0275 RHEUMATOID ARTHRITIS IN HISPANIC PATIENTS: DEMOGRAPHIC AND BASELINE CLINICAL CHARACTERISTICS IN AN EARLY REFERRAL COHORT IN MEXICO VERSUS ROUTINE CARE IN THE UNITED STATES. (June 2019) - Obreja, Elena; Pascual, Virginia Dr.; Riad, Mariam; Contreras-Yáñez, Irazú; Castrejon, Isabel
Abstract : Background: Hispanics are the largest minority group in the United States (US) and his percentage is expected to increase (28.6% by 2060) 1, being Mexicans the largest group (67.9%). RA patients from Latin-America have distinctive features from White patients. The literature highlights a younger age at presentation and a different clinical expression compared with White 2 but few data for Hispanic patients in US are available. Objectives: We compared baseline demographic, clinical features and disease management among Hispanic RA patients from two well characterized cohorts, in the USA and Mexico city. Methods: An early arthritis clinic (EAC) was established at Site 1 (Mexico City); patients with recent-onset RA (<1 year of symptoms) had a standardized assessment and received "treat to target" treatment. At Site 2 (US), a "routine care" cohort was initiated in 2011, and all patients completed a multidimensional health assessment questionnaire (MDHAQ) as part of their routine care. Patients from both sites had baseline complete evaluation including sociodemographic data, patient-reported outcomes (PROs) (patient global assessment, pain-VAS, HAQ/MHAQ, RAPID3), laboratory data, and tender joint counts. Initial treatment was noted. Data from both sites were compared and appropriate statistics was used. Results: 201 patients from site 1 and 179 from site 2 were included (table 1 ); among them, 105 (52%) and 37 (19%), respectively, were DMARDs-naïve at baseline. Patients from site 2 were older and had longer disease duration, however demographic characteristics did not differ. Naïve-DMARDs patients from site 2 scored significantly higher pain-VAS and tender joint counts, and had higher ESR values (p≤0.05, Mann Withney); a similar tendency was seen for other PROs. Time to DMARDs initiation was shorter in the EAC. Conclusion: Hispanic patients with RA from different regions in America may differ in their initial presentation. Naïve DMARDs patients belonging to an early RA cohort had shorter presentation to rheumatology resulting in earlier treatment initiation, which has been associated to better outcomes. EACs facilitate the identification of patients with recent-onset disease and help provide early access to effective therapies. References: [1] Public Health Reviews 2016; 37:31. [2] Best Pract Clin Rheumatol 2008; 22:621-41. Disclosure of Interests: None declared